The reinforcement of sumpah Satie Bukik Marapalam values for character building of students in the learning of history - Piki Setri Pernantah; S Sariyatun; W Warto; A Aisiah (AGASTYA: JURNAL SEJARAH DAN PEMBELAJARANNYA, 2022)
Sumpah Satie Bukik Marapalam is a concept of ideological order that contains a long historical meaning. This text is the local wisdom of the Minangkabau community that contains a moral message and high values to become the philosophy of life of the community. The values contained in the Sumpah Satie Bukik Marapalam can serve as the basis for character formation. The values contained can also be a strengthening attitude in learning in school, contributing to building better student character. Therefore, character development becomes very important through learning, especially through strengthening character values derived from local wisdom carried out in the process of historical learning in schools. This is particularly relevant because historical learning has an important role in the character-building process that seeks to educate students to have more reflective thinking and meaningful learning. The methods used in this study are descriptive-qualitative with a literature study approach and a methodological review between historical learning related to character formation strategies and educational values. This article consists of three steps, as follows: 1) Conduct literature studies and methodological reviews, 2) Analyze literature data and come up with new ideas, 3) report the results of the analysis. This article describes an innovative form of historical learning that is integrated with the strengthening of the local wisdom values of the Minangkabau community so as to contribute to the development of student character. Strengthening the values of local wisdom integrated in the form of religion, responsibility, courage, independence, honor, caring, intellectual, tolerance, movement, and solidarity. In short, this paper formulates other strategies in educational value through historical learning relevant to the goal of historical learning to better shape student character.